Second language writing instruction: A recent practice in Indonesia - Hapsari, Elsa Widya; Sukavatee, P.hD., Pornpimol (Script Journal: Journal of Linguistic and English Teaching, 2018)
Today, a majority of people appear to agree that with the rapid development of English, writing skills cannot be isolated as a standout amongst the most critical skills ((Ali & Hasanah, 2014; Asrifan, 2015). Mustafa and Samad (2015, p. 32) identified two roles of writing for English learners. To start with, it promotes the learnersâ thinking skills, manages their ideas, and enhances their ability in concluding, analyzing and criticizing. Also, it encourages learning, thinking and reflecting on their ability in English. Besides, H Douglas Brown (2007) emphasized that writing is an ability that cannot be produced naturally. Writing is often viewed as a result of the thinking, drafting and revising process that requires particular skills.